Pengaruh Profesionalisme, Pengalaman Auditor, dan Work from Home terhadap Kinerja Auditor (Studi Kasus pada Kantor Akuntan Publik di Jakarta Selatan) - Dian Widiyati; Zubair Jauhamsyah (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2022)
This research aims to determine the Influence of Professionalism, Auditor Experience, and Work From Home on Auditor Performance (Case Study at Public Accounting Firms in South Jakarta). This type of research uses quantitative methods. The population in this study is 12 Public Accounting Firms in South Jakarta. Sampling techniques using convenience sampling techniques are taken based on the availability of elements and the ease of obtaining them, meaning that the information obtained is based on population members who are willing to provide it. The sample in this study amounted to 63 respondents. The data collection method uses the survey method, that is, the author disseminates directly to the respondent. The data analysis techniques in this study used descriptive statistical tests, classical assumption test data quality tests, multiple linear regression tests, and hypothesis tests. Based on the results of spss test version 25 of the tests that have been done showed that simultaneously the variables professionalism, auditor experience, and work from home affect the performance of the auditor. Partially, the professionalism and work from home variables affect the auditor's performance. While the Auditor's Experience has no effect on the Auditor's Performance